Um olhar paranaense sobre o universo artístico no programa caldo de cultura da UFPR TV - Nowisck, Geny Santos (2015)
This research proposes a reflection on cultural journalism on television, specifically targeting at discussing the time given to arts and how the area of arts is treated by the audiovisual media. Therefore, an analysis on the Caldo de Cultura program, broadcast by UFPR-TV –The Federal University Television, located in Curitiba, will be performed; having as the selected and defined corpus four phases of the existing show. Possible negligence on the matter of arts will be questioned, as well as, the restriction on connected issues imposed on artistic manifestations by the television journalism. From the premise that there is a curb when publicizing arts is concerned, specially the art from Parana, in the local media, we try to find hypotheses whether such excluding possibilities are present in the studied show. The methodology that will be used is the quality and quantity analysis, having an analysis-deduction approach which starts from the observation of the selected empiric corpus, by selecting and organizing the data and hints that will guide us to interpretive decisions. The emphasis of the analysis will be on the strategy of the language used on this university TV show and how some shows give room to a differentiated treatment of the arts universe. As for the theoretic basis, we will use the concepts about television developed by Arlindo Machado and Dominique Wolton, as well as Lucia Santaella’s theories on arts and technology, the studies performed by Décio Pignatari about culture, repertoire and television, Jesus Martín-Barbero’s studies on communication and Latin-American culture, the concepts of cultural journalism produced by Daniel Piza, and finally, the sociological studies between cultural practices and social classes produced by Pierre Bordieu, among others. Historical data, articles published in scientific journals and documents available on the internet will be considered when analyzing the information found.